PERLINDUNGAN HUKUM TERHADAP NOTARIS TERKAIT KEWAJIBAN NOTARIS UNTUK MERAHASIAKAN ISI AKTA DALAM PROSES PEMERIKSAAN DI TAHAP PENYIDIKAN - Septio, Dekky; Ismawati, Sri; Agus, Agus (Faculty Of Law, Universitas Tanjungpura, 2023)
AbstractConsumer financing transactions are not only regulated based on the will of the parties, between finance companies and consumers as outlined in a written agreement but are also regulated by several administrative laws and regulations. Agreements are the main legal source of consumer financing in terms of civil law, while the other legal source is Law no. 21 of 2011 and several regulations of the Financial Services Authority also regulate administratively in the form of regulation and supervision of consumer finance companies. Based on the background, the formulation of the problem in this study is about the implementation of the authority of the Financial Services Authority in regulating and supervising consumer finance companies as well as actions for violating the provisions set by the Financial Services Authority against consumer finance companies. The type of research used in this study is normative legal research that uses secondary data supported by supporting data in the form of interviews with the OJK Regional 9 West Kalimantan Representative Office, while the approach used in this research is a statutory approach and a conceptual approach. The form of regulation and supervision that is the authority of the OJK as mandated by Law Number 21 of 2011 concerning the OJK has been implemented in the form of regulations from the Financial Services Authority (POJK) as well as in the form of supervision, both direct supervision and indirect supervision carried out by OJK on companies. consumer finance. Violation of the POJK regulations/stipulations can bring legal consequences to finance companies in the form of administrative sanctions, either in the form of notification or fulfillment of predetermined provisions, written warnings, freezing of business activities and revocation of the financing company's business license. The authority to administer administrative sanctions is obtained based on Law No. 21 of 2011. In addition, if necessary, OJK is also given the authority to take administrative action by providing additional sanctions in the form of restrictions on consumer financing business activities and prohibitions on opening a network of representative branch offices other than branch offices that been there before. AbstrakNegara Indonesia sebagai negara hukum berdasarkan Pancasila dan Undang-Undang dasar Negara Republik Indonesia Tahun 1945 menjamin kepastian, ketertiban, dan perlindungan hukum. Jaminan kepastian, ketertiban, dan perlindungan hukum dalam masyarakat mensyaratkan adanya tulisan sebagai wujud perbuatan, perjanjian, dan ketetapan hukum yang memiliki kekuatan pembuktian terkuat dan terpenuh. Salah satu tulisan yang mempunyai kekuatan pembuktian terkuat dan terpenuh adalah akta notaris. Metode pendekatan yang digunakan dalam penelitian ini adalah yuridis normatif yang mana dalam pembahasan objek penelitian ini menitik beratkan terhadap data kepustakaan (penelahaan terhadap literatur) dan data sekunder, dimana dalam menganalisa data dari objek penelitian dengan mengunakan teori-teori hukum dan ketentuan perundang-undangan yang berlaku dalam memnganalisa permasalahan yang akan diteliti pesifikasi penelitian yang digunakan adalah deskriptif analitis, yaitu suatu penelitian yang bertuuan memberikan gambaran fakta mengenai permasalahan-permasalahan terkait dengan kerahasiaan akta yang dibuat seorang Notaris dalam memerikan keterangan terkait putusan Mahkamah Konstitusi Nomor 49/PUU-X/2012, peneliti beru menggambarkan suatu keadaan tentang adanya pembaharuan terhadap undang-undang Notaris guna demi perlindungan hukum terhadap Notaris dalam menjalankan tugas jabatanya serta perlindungan hak-hak Notaris yang telah ditentukan oleh undang-undang. Berdasarkan Ketentuan Undang-Undang Jabatan Notaris Pasal 1 angka 1 UUJN menyebutkan bahwa Notaris adalah